EFFECT OF LYMPHOKINES ON DRUG RESISTANCE OF BREAST TUMOR - L. T. Alimkhodzhayeva (Опухоли женской репродуктивной системы)
The paper considers the effect of cytokines isolated from autologous peripheral lymphocytes on the kinetics of breast cancer, which is exhibited by induced apoptosis and inhibited proliferation. The effect achieved leads to the conclusion that the isolated cytokines have antitumor action.